Individual attitudes towards immigration in aging populations - Rana Comertpay; Andreas Irmen; Anastasia Litina (Center for Economic Studies and ifo Institute (CESifo), 2019)
This research empirically establishes the hypothesis that the process of population aging in a society as a whole affects the attitudes of its members towards immigration. Hence, an aging social environment exerts an effect on the attitudes of individuals towards immigration after accounting for their age and other individual characteristics. We test this hypothesis in a multilevel analysis of individuals living in 25 European OECD countries over the period 2002-2017. Our measure of “societal population aging” is the old-age dependency ratio. “Attitudes” are taken from immigration related questions in eight consecutive rounds of the European Social Survey. For these attitudes we find non-linear, U-shaped relationships. Hence, the effect of societal population aging on individual attitudes towards immigration is negative in young societies and positive in old ones.
Keywords: J10; Z10; 330; population aging; attitudes; immigration; culture